Aluminum doping effects on photoresponse characteristics of hydrothermal tin disulfide nanosheets. Issue 26 (18th June 2021) - Meng, Xiancheng; Fan, Chao; An, Xia; Yuan, Shuo; Jing, Yongkai; Liu, Zhe; Sun, Chun; Zhang, Yonghui; Zhang, Zihui; Wang, Mengjun; Zheng, Hongxing; Li, Erping
Abstract : Photoresponse characteristics of Al-doped SnS2 nanosheets have been improved significantly by aluminum doping, compared to pristine SnS2 . The response time was reduced by two orders of magnitude and the responsivity was increased one hundredfold. Abstract : Tin disulfide has attracted enormous interest due to its excellent optical and electronic properties for future optoelectronic applications, especially high-performance photodetectors. Nevertheless, SnS2 -based photodetectors still face great challenges for practical applications, such as low responsivity and slow response speed. Herein, the enhanced photoresponse characteristics of aluminum (Al)-doped SnS2 nanosheets were investigated. Al-doped SnS2 nanosheets were synthesized by using a convenient and high-yield hydrothermal technique, and high purity and high crystallinity were confirmed by SEM, XRD, Raman spectroscopy, XPS, and TEM. Al atoms were homogeneously introduced into SnS2 nanosheets, leading to a slight increase in lateral size from 185.4 nm to 196.9 nm and thickness from 13.5 nm to 17.9 nm. Then, photodetectors based on Al-doped SnS2 nanosheets were built and characterized. Compared to pristine SnS2, the photoresponse performance of the Al-doped SnS2 nanosheets was significantly improved. In particular, the response time was reduced by nearly two orders of magnitude from 1040 ms to 51 ms. The responsivity was increased one hundredfold, from 0.79 mA W −1 to 15.16 mA W −1 . The photoresponse characteristics are prominently enhanced due to Al-doping induced band gap narrowing. Our findings provide an effective approach to improve the photoresponse performance of SnS2 and pave the way for further optoelectronic applications of SnS2 .